High-performance photovoltaic junction box pouring sealant and preparation method thereof

By adopting a two-component structure in the photovoltaic junction box potting glue, combined with specific components and preparation methods, the existing potting glue is solved, and the problem of difficulty in meeting the adhesive, thermal conductivity, water resistance and insulation at the same time is realized, and the high-performance photovoltaic junction box potting glue is significantly extended.

CN119684961APending Publication Date: 2025-03-25JIANGSU TIANCHEN NEW MATERIALS

Patent Information

Application Number
CN202411857050.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicone potting glue is difficult to meet excellent adhesion, thermal conductivity, water resistance and insulation in photovoltaic junction boxes, which limits its application range in the photovoltaic industry.

Method used

A high-performance photovoltaic junction box potting adhesive with a two-component structure, component A includes α,ω-dihydroxypolydimethylsiloxane, fillers, plasticizers, modifiers and additives, and component B includes dimethylsilicone oil, curing agents, coupling agents and catalysts. Through specific component ratios and preparation methods, the adhesiveness, water barrier and insulating properties of the potting adhesive are improved.

Benefits of technology

On the premise of ensuring mechanical properties, flow properties and curing properties, the adhesiveness, water resistance and insulation of the potting glue are significantly enhanced. The silicone potting glue provided has good sealing reliability and weather resistance, extending the service life of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192117980000081
    Figure BDA0005192117980000081
  • Figure BDA0005192117980000082
    Figure BDA0005192117980000082
  • Figure BDA0005192117980000091
    Figure BDA0005192117980000091
Patent Text Reader

Abstract

The invention discloses a high-performance photovoltaic junction box pouring sealant and a preparation method, and relates to the technical field of two-component condensed type organosilicone, the high-performance photovoltaic junction box pouring sealant comprises a component A and a component B. The component A comprises 40-50 parts of alpha, omega-dihydroxy polydimethylsiloxane, 40-50 parts of a filler, 5-10 parts of a plasticizer, 5-10 parts of a modifier and 0.02-0.1 part of an auxiliary agent; the component B comprises 30-50 parts of dimethyl silicone oil, 20-30 parts of a curing agent, 10-20 parts of a coupling agent and 0.04-1 part of a catalyst, the viscosity of alpha, omega-dihydroxy polydimethylsiloxane is 1000-3000 cp, the filler is selected from silicon dioxide, calcium carbonate, aluminum oxide, aluminum hydroxide, kaolin, mica and talcum powder, and the plasticizer is one or more of dimethyl silicone oil and polyether modified silicone oil. According to the high-performance photovoltaic junction box pouring sealant and the preparation method, the pouring sealant prepared by the invention is short in curing time, has good weather resistance, adhesion and insulativity, is excellent in heat-conducting property and flame-retardant property, and is suitable for marine photovoltaic module packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of two-component condensation type organic silicon, in particular to a high-performance photovoltaic junction box potting adhesive and a preparation method thereof. Background Art

[0002] The photovoltaic junction box is a connector between photovoltaic cells and solar control systems. It plays a bridging role in current signal transmission and is an important photovoltaic component. However, since photovoltaic integrated components are often installed in environments with high temperature, high humidity, sandstorms, high light, salt spray, snow, hail, etc., the components are susceptible to severe aging and corrosion. Therefore, in order to protect the photovoltaic junction box and the overall service life of the photovoltaic component, various potting glues are often used to seal the inside of the junction box to enhance the oxidation resistance, impact resistance and weather resistance of the junction box. At the same time, since the electrothermal effect of electronic components will generate heat energy, the potting glue in the junction box needs to have good adhesion, weather resistance, insulation, thermal conductivity and flame retardancy.

[0003] The main component of silicone potting glue is polysiloxane. As a commonly used organic high-molecular-weight material, its structure is mainly based on the high cross-linking of Si-O-Si. The Si-O bond has the characteristics of high bond energy, low surface energy, and low glass transition temperature. The main chain has good flexibility, which gives the silicone potting glue good weather resistance, flame retardancy, insulation and waterproofness, making it very suitable for the potting of junction boxes. Silicone potting glue mainly includes two-component addition-type silicone potting glue and condensation-type potting glue. Among them, condensation-type potting glue is more suitable for the potting of photovoltaic module junction boxes because of its better adhesion, wider application range, and relatively low cost;

[0004] With the continuous expansion of the application field of photovoltaic modules in recent years, sea and island photovoltaics not only need to have good insulation and sealing effects on the junction box, but also need to have more excellent water-blocking properties to ensure the safe use of photovoltaic modules. In recent years, there have been many reports on conventional silicone potting adhesives, but there are few reports on silicone photovoltaic junction box potting adhesives with better water-blocking, adhesion and insulation properties.

[0005] The existing publication number CN106833501A provides a two-component silicone potting glue and provides a preparation method thereof. The above-mentioned potting glue contains hydroxyl-terminated polydimethylsiloxane, inorganic filler, plasticizer, deep curing accelerator, crosslinking agent, coupling agent and catalyst. Through physical modification and adding aluminum hydroxide and aluminum oxide with flame retardancy and thermal conductivity, the thermal conductivity of the potting glue is improved, and the performance of the composite silicone itself is met to meet the basic potting requirements. However, it does not improve its adhesion and water barrier properties in the molecular structure, which limits its application scope in the photovoltaic industry.

[0006] On this basis, it is of great significance to develop a silicone potting glue that can simultaneously meet the requirements of excellent bonding performance, thermal conductivity, water barrier properties, and insulation. The existing publication number CN116083042A provides a two-component potting glue containing phenyl. The above-mentioned potting glue includes component A and component B, wherein component A includes terminal hydroxyl polydimethylsiloxane, terminal hydroxyl polymethylphenylsiloxane, plasticizer, filler, deep curing agent, and component B contains a cross-linking agent, a coupling agent, a plasticizer, and a catalyst. It further improves the water barrier properties of the potting glue by introducing a phenyl-containing base polymer, but its adhesion and insulation properties are still defective. For this reason, in view of the above problems, a high-performance photovoltaic junction box potting glue and a preparation method are now designed to better meet the actual use needs. Summary of the invention

[0007] The purpose of the present invention is to provide a high-performance photovoltaic junction box potting adhesive and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0008] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-performance photovoltaic junction box potting glue, comprising component A and component B, component A comprises 40-50 parts of α, ω-dihydroxy polydimethylsiloxane, 40-50 parts of filler, 5-10 parts of plasticizer, 5-10 parts of modifier, and 0.02-0.1 parts of auxiliary agent; component B comprises 30-50 parts of dimethyl silicone oil, 20-30 parts of curing agent, 10-20 parts of coupling agent, and 0.04-1 part of catalyst, and the viscosity of the α, ω-dihydroxy polydimethylsiloxane is 1000-3000cp.

[0009] Preferably, the filler is selected from silicon dioxide, calcium carbonate, aluminum oxide, aluminum hydroxide, kaolin, mica, and talc.

[0010] Preferably, the plasticizer is one or more of dimethyl silicone oil and polyether-modified silicone oil.

[0011] Preferably, the deep curing agent is one or more of deionized water, hydrated calcium chloride, hydrated aluminum oxide and hydrated calcium sulfate.

[0012] Preferably, the modifier is one or more of hydroxyl-terminated polybutadiene, isocyanate-terminated polybutadiene and carboxyl-terminated polybutadiene.

[0013] Preferably, the crosslinking agent is one or more of methyl orthosilicate, ethyl orthosilicate, ethyl orthosilicate oligomer, methyltrimethoxysilane, methyltriethoxysilane and methyltriethoxysilane oligomer.

[0014] Preferably, the coupling agent is one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0015] Preferably, the catalyst is one or more of dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate and chelated tin.

[0016] Preferably, the auxiliary agent is one or more of titanium dioxide and ultramarine blue.

[0017] Preferably, the preparation method of the high-performance photovoltaic junction box potting adhesive comprises the following steps:

[0018] (1) Preparation of component A: α,ω-dihydroxy polydimethylsiloxane, plasticizer, modifier, auxiliary agent and modified filler are fully mixed and stirred, and then a deep curing agent is added and fully mixed and stirred at a stirring speed of 30-50 rpm, and then vacuumed and mixed at the same speed to obtain component A, with a mixing time of 1 h to 1.5 h and a mixing pressure of -0.10 to 0.08 MPa;

[0019] (2) Preparation of component B: The crosslinking agent and the coupling agent are fully mixed in proportion to form a mixed solution for 0.5 h to 1 h. The plasticizer and the catalyst are then simply mixed and then slowly added dropwise to the mixed solution under a nitrogen atmosphere. After the addition is complete, the mixture is fully stirred and mixed at a pressure of -0.10 to -0.08 MPa. The stirring is then stopped and the mixture is reacted under vacuum for 20 to 40 min to obtain component B.

[0020] (3) Preparation of organic potting compound: Component A and component B are mixed in corresponding proportions to obtain an organic potting compound.

[0021] Compared with the prior art, the present invention has the following beneficial effects: the high-performance photovoltaic junction box potting glue and preparation method can greatly enhance the adhesion, water barrier and insulation of the potting glue while ensuring its mechanical properties, flow properties and curing properties. The provided silicone potting glue has a volume resistivity greater than 1×10 15 , cohesive failure rate is 100%, the silicone potting glue has good water-blocking effect;

[0022] The organic silicone potting glue has good sealing reliability, which can ensure that the photovoltaic junction box components are protected from external media during service and extend the service life of the photovoltaic components. The potting glue has good fluidity and curing properties, is compatible with the existing gluing process, and quickly completes the sealing of the junction box. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] The present invention provides a technical solution: a high-performance photovoltaic junction box potting glue and a preparation method. In the present invention, unless otherwise specified, all raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.

[0025] The following is the test method of the performance parameters involved in the present invention:

[0026] (1) Viscosity: The viscosity of component A before mixing the potting compound is tested according to GB-T 2794.

[0027] (2) Density: The density of the potting compound is tested according to GB / T 4472-84.

[0028] (3) Surface drying time: measured according to GB / T 13477.5

[0029] (4) Gel time: measured according to standard GB / T 7193.6

[0030] (5) Hardness: Test the hardness of the potting compound according to GB / T 531.

[0031] (6) Volume resistivity: measured according to GB / T 1692

[0032] (7) Tensile strength: The tensile strength of the potting compound is tested according to GB / T 528.

[0033] (8) Elongation at break: The tensile strength of the potting compound is tested according to GB / T 528.

[0034] (9) Adhesion performance: After curing for 7 days at (23±2)℃ and (50±5)% humidity, the adhesion performance of the two-component silicone potting adhesive and the junction box was tested using GB / T 29595.

[0035] (10) High temperature and high humidity resistance: at a temperature of 105°C, a humidity of 100% RH, and a pressure of 1.21 kg / cm 2 Keep the temperature for 48 hours and observe whether the potting junction box has any powdering, cracking or yellowing.

[0036] In the following examples and comparative examples, component A and component B were prepared according to the following methods:

[0037] Preparation of component A: Add terminal hydroxyl polydimethylsiloxane, plasticizer, modifier, additive and modified filler in a planetary mixer in sequence, stir at 10 rpm for 10 min, then stir at 30 rpm for 20 min, then mix at 40 rpm for 30 min under a vacuum degree of -0.095 MPa, then add deep curing agent, mix at 40 rpm for 15 min, and finally degas under a vacuum degree of -0.095 MPa to obtain component A;

[0038] Preparation of component B: add the crosslinking agent and coupling agent to the planetary mixer in sequence, mix at a stirring speed of 40 rpm for 15 minutes at a vacuum degree of -0.095 MPa. First, simply mix the plasticizer and catalyst with a glass rod, add them to the mixer under nitrogen protection, and then stir at a speed of 40 rpm for 15 minutes at a vacuum degree of -0.095 MPa. Finally, stop stirring and react under vacuum for 30 minutes to obtain component B.

[0039] Example 1

[0040] In this embodiment, component A includes: 47 parts by weight of terminal hydroxyl polydimethylsiloxane, with a viscosity of 1500 mPa·s at 23°C; 15 parts by weight of dimethyl silicone oil, with a viscosity of 350 mPa·s at 23°C; 3 parts by weight of terminal hydroxyl polybutadiene, with a viscosity of 1000 mPa·s at 23°C; 40 parts by weight of aluminum hydroxide, with an average particle size of 5 μm; 1 part by weight of bentonite, with an average particle size of 18 μm; and 0.1 parts by weight of deionized water as a deep curing agent. These components are mixed according to the above method for preparing component A to obtain component A, and its viscosity and density are tested. The results are shown in Table 1 below.

[0041] Component B: 50 parts by weight of dimethyl silicone oil, viscosity at 23°C 100 mPa·s; crosslinking agent: 6 parts by weight of methyltriethoxysilane, 612 parts by weight of polytetraethoxysilane, 6 parts by weight of methyltriethoxysilane oligomer; coupling agent: 8 parts by weight of γ-aminopropyltrimethoxysilane N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, 12 parts by weight of aminosilane oligomer; 0.84 parts by weight of dibutyltin dilaurate. These components were mixed according to the method for preparing component B above to obtain component B, and its viscosity was tested. The results are shown in Table 1 below.

[0042] Component A and component B were mixed evenly at a mass ratio of 6:1, and after curing, a silicone potting adhesive was formed. The relevant properties were then tested according to the above method. The results are shown in Tables 1 and 2 below.

[0043] Example 2

[0044] In this embodiment, component A includes: 44 parts by weight of terminal hydroxyl polydimethylsiloxane, with a viscosity of 1500 mPa·s at 23°C; 15 parts by weight of dimethyl silicone oil, with a viscosity of 350 mPa·s at 23°C; 6 parts by weight of terminal hydroxyl polybutadiene, with a viscosity of 1000 mPa·s at 23°C; 40 parts by weight of aluminum hydroxide, with an average particle size of 5 μm; 1 part by weight of bentonite, with an average particle size of 18 μm; and 0.1 parts by weight of deionized water as a deep curing agent. These components are mixed according to the above method for preparing component A to obtain component A, and its relevant properties are tested. The results are shown in Table 1 below.

[0045] Component B: 50 parts by weight of dimethyl silicone oil, viscosity at 23°C 100 mPa·s; crosslinking agent: 6 parts by weight of methyltriethoxysilane, 12 parts by weight of polytetraethoxysilane; coupling agent: 8 parts by weight of γ-aminopropyltrimethoxysilane, 12 parts by weight of aminosilane oligomer; 0.4 parts by weight of dibutyltin dilaurate. These components were mixed according to the above method for preparing component B to obtain component B, and its viscosity was tested. The results are shown in Tables 1 and 2 below.

[0046] Component A and component B were mixed evenly at a mass ratio of 6:1, and after curing, an organic silicone potting adhesive was formed. Then, the relevant properties were tested according to the above method. The results are shown in Table 1 below.

[0047] Example 3

[0048] In this embodiment, component A includes: 41 parts by weight of terminal hydroxyl polydimethylsiloxane, with a viscosity of 1500 mPa·s at 23°C; 15 parts by weight of dimethyl silicone oil, with a viscosity of 350 mPa·s at 23°C; 9 parts by weight of terminal hydroxyl polybutadiene, with a viscosity of 1000 mPa·s at 23°C; 40 parts by weight of aluminum hydroxide, with an average particle size of 5 μm; 1 part by weight of bentonite, with an average particle size of 18 μm; and 0.1 parts by weight of deionized water as a deep curing agent. These components are mixed according to the method for preparing component A described above to obtain component A, and its viscosity and density are tested. The results are shown in Table 1 below.

[0049] Component B: 50 parts by weight of dimethyl silicone oil, viscosity at 23°C 100 mPa·s; crosslinking agent: 6 parts by weight of methyltriethoxysilane, 12 parts by weight of polytetraethoxysilane; coupling agent: 8 parts by weight of γ-aminopropyltrimethoxysilane, 12 parts by weight of aminosilane oligomer; 0.4 parts by weight of dibutyltin dilaurate. These components were mixed according to the method for preparing component B above to obtain component B, and its viscosity was tested. The results are shown in Table 1 below.

[0050] Component A and component B were mixed evenly at a mass ratio of 6:1, and after curing, a silicone potting adhesive was formed. The relevant properties were then tested according to the above method. The results are shown in Tables 1 and 2 below.

[0051] Comparative Example 1

[0052] In this embodiment, component A includes: 40 parts by weight of hydroxy-terminated polydimethylsiloxane, with a viscosity of 1500 mPa·s at 23°C; 15 parts by weight of dimethyl silicone oil, with a viscosity of 350 mPa·s at 23°C; 40 parts by weight of aluminum hydroxide, with an average particle size of 5 μm; and 1 part by weight of bentonite, with an average particle size of 18 μm. These components are mixed according to the above method for preparing component A to obtain component A, and its viscosity and density are tested. The results are shown in Table 1 below.

[0053] Component B: 50 parts by weight of dimethyl silicone oil, viscosity at 23°C 100 mPa·s; crosslinking agent: 6 parts by weight of methyltriethoxysilane, 12 parts by weight of polytetraethoxysilane; coupling agent: 8 parts by weight of γ-aminopropyltrimethoxysilane, 12 parts by weight of aminosilane oligomer; 0.4 parts by weight of dibutyltin dilaurate. These components were mixed according to the method for preparing component B above to obtain component B, and its viscosity was tested. The results are shown in Table 1 below.

[0054] Component A and component B were mixed evenly at a mass ratio of 6:1, and after curing, a silicone potting adhesive was formed. The relevant properties were then tested according to the above method. The results are shown in Tables 1 and 2 below.

[0055] Comparative Example 2

[0056] Component A and component B were prepared according to the ratio of Example 3, except that no hydroxyl-terminated polydimethylsiloxane was used. 49 parts by weight of hydroxyl-terminated polydimethylsiloxane was used. The relevant properties are shown in Tables 1 and 2 below.

[0057] Table 1

[0058]

[0059] Table 2

[0060]

[0061]

[0062] In the prior art, the potting adhesive for photovoltaic junction boxes is required to have good water resistance, insulation and adhesion.

[0063] The test results of Table 1 and Table 2 show that, by adding a certain amount of hydroxyl-terminated polybutadiene to component A, the organosilicon potting adhesive prepared in Example 3 has a high volume resistivity, a cohesive failure rate of 100, and substantially no change in appearance after Hast high temperature and high humidity accelerated aging, has good sealing, and good flexibility. However, since the industry requires a hardness of 30-60shoer A, a too large hardness is likely to produce large temperature stress and damage the junction box components, while a too small hardness is subject to external force, causing deformation of the junction box and damaging the junction box components. Therefore, Example 2 is recommended as the best choice, which has good mechanical properties and excellent performance.

[0064] In Example 1, no deep curing agent was added, and the gel time was long. However, after adding the deep curing agent in Example 2, the gel time was greatly shortened. The industry requires the gel time to be ≤70min. It can be seen that the deep curing agent is

[0065] Good gel time regulation method.

[0066] In the technical solution disclosed in the present invention, bentonite with a layered structure is further added to component A, which can be used as a partial substitute for aluminum hydroxide and synergistically flame retardant with aluminum hydroxide to reduce product costs.

[0067] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A high-performance photovoltaic junction box potting glue, characterized in that: The invention comprises component A and component B, wherein component A comprises 40-50 parts of α,ω-dihydroxy polydimethylsiloxane, 40-50 parts of filler, 5-10 parts of plasticizer, 5-10 parts of modifier and 0.02-0.1 parts of auxiliary agent; component B comprises 30-50 parts of dimethyl silicone oil, 20-30 parts of curing agent, 10-20 parts of coupling agent and 0.04-1 parts of catalyst, and the viscosity of the α,ω-dihydroxy polydimethylsiloxane is 1000-3000cp.

2. A high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The fillers include silicon dioxide, calcium carbonate, alumina, aluminum hydroxide, kaolin, mica, and talc.

3. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The plasticizer is one or more of dimethyl silicone oil and polyether modified silicone oil.

4. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The deep curing agent is one or more of deionized water, hydrated calcium chloride, hydrated aluminum oxide and hydrated calcium sulfate.

5. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The modifier is one or more of hydroxyl-terminated polybutadiene, isocyanate-terminated polybutadiene and carboxyl-terminated polybutadiene.

6. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The crosslinking agent is one or more of methyl orthosilicate, ethyl orthosilicate, ethyl orthosilicate oligomer, methyltrimethoxysilane, methyltriethoxysilane and methyltriethoxysilane oligomer.

7. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The coupling agent is one or more of gamma-aminopropyltrimethoxysilane, gamma-aminopropyltriethoxysilane, N-beta-aminoethyl-gamma-aminopropyltrimethoxysilane and gamma-glycidyloxypropyltrimethoxysilane.

8. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The catalyst is one or more of dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate and chelated tin.

9. The high-performance photovoltaic junction box potting adhesive according to claim 1, characterized in that: The auxiliary agent is one or more of titanium dioxide and ultramarine blue.

10. A method for preparing a high-performance photovoltaic junction box potting adhesive as claimed in any one of claims 1 to 9, characterized in that: The steps are as follows: (1) Preparation of component A: α,ω-dihydroxy polydimethylsiloxane, plasticizer, modifier, auxiliary agent and modified filler are fully mixed and stirred, and then a deep curing agent is added and fully mixed and stirred at a stirring speed of 30-50 rpm, and then vacuumed and mixed at the same speed to obtain component A, with a mixing time of 1 h to 1.5 h and a mixing pressure of -0.10 to 0.08 MPa; (2) Preparation of component B: The crosslinking agent and the coupling agent are fully mixed in proportion to form a mixed solution for 0.5 h to 1 h. The plasticizer and the catalyst are then simply mixed and then slowly added dropwise to the mixed solution under a nitrogen atmosphere. After the addition is complete, the mixture is fully stirred and mixed at a pressure of -0.10 to -0.08 MPa. The stirring is then stopped and the mixture is reacted under vacuum for 20 to 40 min to obtain component B. (3) Preparation of organic potting compound: Component A and component B are mixed in corresponding proportions to obtain an organic potting compound.

Citation Information

Patent Citations

  • Bi-component organosilicon pouring sealant, and preparation method and application thereof

    CN106833501A

  • Two-component organic silicon pouring sealant and application thereof

    CN116083042A

  • Modified two-component silicone sealant and preparation method thereof

    CN109971416A

  • Sealant as well as preparation method and application thereof

    CN116554832A

  • Double-glass assembly frame sealant and preparation method thereof

    CN118599471A

Cited By

  • Flame-retardant moistureproof and anti-condensation plugging group material as well as preparation method and application thereof

    CN120607815A

  • Mixing tube anti-curing pouring sealant for junction box and preparation method thereof

    CN121780112A